Manager Divestment in Leveraged Buyouts. (17th June 2013) - Ang, James; Hutton, Irena; Majadillas, Mary Anne
Abstract We examine changes in managers' investment in the firm around leveraged buyouts and find agency costs counter to those described in extant literature. In majority of deals during 1997–2008, managers divested a portion of their pre‐LBO shareholdings while maintaining an ownership stake in the post‐LBO firm. Such divestment opportunities encourage managers to behave in a way that benefits existing shareholders but is costly to new investors. We report a positive relation between management's divestment and pre‐LBO earnings management, market timing, and better buyout pricing. Although managerial divestment also leads to subpar post‐buyout performance, the involvement of private equity mitigates it.